2005
DOI: 10.1007/s11418-005-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triterpene compounds on cytotoxicity, apoptosis, and immune response in cultured cells

Abstract: To identify a candidate compound for therapy of chronic viral hepatitis, we screened a series of oleanene-type triterpenoids for their ability to alleviate aflatoxin B 1 (AFB)-induced cytotoxicity, protect against actinomycin-tumor necrosis factor-induced apoptosis, and modulate the mixed lymphocyte reaction (MLR) in cultured cells. Glycyrrhizin at 200 lg/ml showed the strongest inhibitory effects on cytotoxicity without an immunomodulatory effect on MLR. In comparison, glycyrrhetic acid, the aglycone of glycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…found that OCA protected against hepatocyte death and liver fibrosis in a murine model of NASH. [ 45 ] Evidences from both in vitro experiments [ 32,33,46,47 ] and in vivo animal studies [ 29–31 ] supported that soyasaponins have hepatoprotective bioactivities. Furthermore, different structures of soyasaponins vary in their hepatoprotective bioactivities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that OCA protected against hepatocyte death and liver fibrosis in a murine model of NASH. [ 45 ] Evidences from both in vitro experiments [ 32,33,46,47 ] and in vivo animal studies [ 29–31 ] supported that soyasaponins have hepatoprotective bioactivities. Furthermore, different structures of soyasaponins vary in their hepatoprotective bioactivities.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Moreover, soyasapogenol A and soyasapogenol B could protect against aflatoxin B 1 -induced cytotoxicity to liver cells. [33] Hong et al found that soybean embryo powder containing bioactive substances such as isoflavones and soyasaponins exhibited hepatoprotective effects by enhancing adiponectin-mediated AMP-activated protein kinase (AMPK) pathway in high-fat and high-cholesterol diet-induced NAFLD mice and suggested that the regular supplementation of this powder might be a useful treatment for preventing NAFLD and associated complications. [34] Our recent study found that SS (A 1 , A 2 , and I) alleviated the hepatic steatosis and inflammation in high-fat diet (HFD)-induced C57BL/6J obese mice.…”
Section: Introductionmentioning
confidence: 99%
“…Pentacyclic triterpenoids, as a class of bioactive natural products, are abundant in many plants in the form of free acids or aglycones . Generally, they consist of six isoprene units with multiple functional groups, unique chiral centers, rigid skeletons, and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Pentacyclict riterpenoids,a saclass of bioactive naturalp roducts, are abundant in many plants in the form of free acids or aglycones. [1][2][3][4][5] Generally,t hey consist of six isoprene units with multiple functional groups, unique chiral centers, rigids keletons, and good biocompatibility.T hese features not only endow them with pharmacological properties, [6][7][8][9] but also make them ideal building blocks fors elf-assembling versatile supramolecular structures. [10][11][12][13] Since the first supramolecular organogel based on ap entacyclic triterpenoid was reported by Bag and co-workers in 2005, [14] as eries of pentacyclic triterpe-noid-based smallm olecules have been designed and synthesized to study their supramolecular gelation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They have attracted signicant attention over the past decades due to their relative low-toxicity and prominent biological activities in anti-virus, anti-tumor, and anti-inammatory. [4][5][6][7][8] Recently, increasing efforts have been made to fabricate supramolecular assemblies on account of their multiple functional groups, rigid skeleton, and unique stacking manners. [9][10][11][12][13][14][15] These features render triterpenoids as one of the ideal building blocks for constructing supramolecular structures by the self-assembly.…”
mentioning
confidence: 99%